El empleador plural: articulación jurídica y responsabilidades (Milan Law Review, 2020)
The author focuses on the controversial figure of the plural employer recognised by the Spanish legal system, not only at the regulatory level, but also at the jurisprudential one, considering it a preferential formula for inter-company cooperation, especially following the development of global production processes dominated by the rise of business groups and networks. The contribution explores the numerous legal profiles as well as the tricky problems that arise from the unique configuration of the complex employment relationship, where the worker, is the only debtor and creditor of the salary, but employers are more than one.
Keywords: Plural employer – Codatoriality – Enterprise groups – Business networks – Complex obligations – Employment relationship